2011
DOI: 10.1523/jneurosci.5980-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Different Pain, Different Brain: Thalamic Anatomy in Neuropathic and Non-Neuropathic Chronic Pain Syndromes

Abstract: Trigeminal neuropathic pain (TNP) and temporomandibular disorders (TMD) are thought to have fundamentally different etiologies. It has been proposed that TNP arises through damage to, or pressure on, somatosensory afferents in the trigeminal nerve, whereas TMD results primarily from peripheral nociceptor activation. Because some reports suggest that neuropathic pain is associated with changes in brain anatomy, it is possible that TNP is maintained by changes in higher brain structures, whereas TMD is not. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
183
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(204 citation statements)
references
References 40 publications
18
183
3
Order By: Relevance
“…Thalamic reorganization occurs following sectioning of peripheral afferents (Garraghty et al, 1991), sensory thalamus stump representations expand in amputees (Davis et al, 1998), and, following complete spinal cord injury, ventral thalamus cells that would normally respond to inputs from upper extremities respond to inputs from the neck and occiput (Lenz et al, 1987). Since neuropathic pain conditions are associated with changes in thalamic anatomy and biochemistry (Pattany et al, 2002;Gustin et al, 2010Gustin et al, , 2011 and thalamic lesions often result in neuropathic pain (Klit et al, 2009), changes in thalamic function may result in neuropathic pain by altering firing patterns of thalamocortical loops (Sarnthein and Jeanmonod, 2008).…”
Section: Figure6mentioning
confidence: 99%
“…Thalamic reorganization occurs following sectioning of peripheral afferents (Garraghty et al, 1991), sensory thalamus stump representations expand in amputees (Davis et al, 1998), and, following complete spinal cord injury, ventral thalamus cells that would normally respond to inputs from upper extremities respond to inputs from the neck and occiput (Lenz et al, 1987). Since neuropathic pain conditions are associated with changes in thalamic anatomy and biochemistry (Pattany et al, 2002;Gustin et al, 2010Gustin et al, , 2011 and thalamic lesions often result in neuropathic pain (Klit et al, 2009), changes in thalamic function may result in neuropathic pain by altering firing patterns of thalamocortical loops (Sarnthein and Jeanmonod, 2008).…”
Section: Figure6mentioning
confidence: 99%
“…There is increasing evidence that TNP is associated with anatomical and biochemical changes in the thalamus (14)(15)(16). Moreover, patients with TNP display significant reductions in thalamic volume and neural viability (15), indicating that altered thalamic anatomy, physiology, and biochemistry may result in disturbed thalamocortical oscillatory properties.…”
mentioning
confidence: 99%
“…Abnormal thalamic activity has been investigated in patients with neuropathic pain (3-7, 10-13, 17, 18), including TNP (14)(15)(16). Furthermore, the potential role of thalamic burst firing in abnormally increased low-frequency oscillations has been proposed as a pathophysiological mechanism (2,12).…”
mentioning
confidence: 99%
“…In contrast, localised thalamic atrophy was detected in trigeminal neuropathy, but not in patients that were classified as having trigeminal neuralgia or temporomandibular disorders [80]. Using MR spectroscopy in the same study, reduced levels of N-acetyl-aspartate, a marker of neuronal viability was found in the affected thalami.…”
Section: Thalamic Volumetrymentioning
confidence: 84%
“…Using MR spectroscopy in the same study, reduced levels of N-acetyl-aspartate, a marker of neuronal viability was found in the affected thalami. The difference between the direction of thalamic volume changes in trigeminal neuropathy and other pain disorder in the trigeminal territory may lie in the different pathomechanisms; peripheral events were proposed in trigeminal neuralgia and temporomandibular disorder, while the reduced volume and neural viability suggest central mechanisms in trigeminal neuropathy [80]. In a recent study on trigeminal neuralgia gray matter volume reduction was described in the thalamus, insula, anterior cingulate cortex, primary somatosensory and orbitofrontal cortices, secondary somatosensory cortex, cerebellum, and dorsolateral prefrontal cortex [81].…”
Section: Thalamic Volumetrymentioning
confidence: 99%